2013
DOI: 10.1128/jcm.01581-13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of BD Phoenix and Vitek 2 Systems for Species Identification of Common and Uncommon Pathogenic Yeasts

Abstract: The BD Phoenix system was evaluated for species-level identification of yeasts (250 clinical isolates) and compared with the Vitek 2 system, using ribosomal internal transcribed spacer (ITS) sequence analysis as the gold standard. Considering only the species included in each system's database, 96.3% (236/245) and 91.4% (224/245) of the isolates were correctly identified by BD Phoenix and Vitek 2, respectively. During the last decades, the growing number of vulnerable hosts such as critically ill or otherwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
1
12
1
7
Order By: Relevance
“…It is widely recognized that commercial biochemical systems have limited accuracy in identifying rare yeast species (accuracy, 50 to 65%) (14)(15)(16). The present study further confirms these findings, as the Vitek 2 system was highly unreliable in the identification of C. laurentii.…”
supporting
confidence: 80%
“…It is widely recognized that commercial biochemical systems have limited accuracy in identifying rare yeast species (accuracy, 50 to 65%) (14)(15)(16). The present study further confirms these findings, as the Vitek 2 system was highly unreliable in the identification of C. laurentii.…”
supporting
confidence: 80%
“…Phoenix Yeast ID Panelin C.albicans'ı tanımlama oranı, API ID 32C'den biraz düşük (%92) olsa da aralarında anlamlı bir fark yoktur. Bu sistemin, Vitek 2 kolorimetrik YST kart ile karşılaştırıldığı benzer bir çalışmada, C.albicans suşları için %98 oranında uyumluluk saptanmıştır 18 . API ID 32C ile C.kefyr olarak tanımlanan ve morfolojik incelemeyle desteklenen altı izolat, Phoenix Yeast ID Panel tarafından S.cereviciae olarak tanımlanmıştır (Tablo I).…”
Section: Discussionunclassified
“…Ayrıca iki ticari tanımlama sistemi üretici firmaların önerileri doğrultusunda çalışıldı, sonuçların birbirleriyle uyumları karşılaştırıldı ve morfolojik bulguların tanımlamaya etkisi incelendi. Çalışmada değerlendirilen yöntemlerden biri, sadece asimilasyona dayanan ve birçok çalışmada kullanılmış güvenilir bir tanım-lama sistemi 14 olan API  ID 32C (bioMerieux, Fransa); diğeri ise asimilasyonun yanı sıra enzimatik reaksiyonları da kullanan, daha yeni ve deneyimin az olduğu tanımlama sistemi 18 Her iki sistemle farklı sonuç veren 27 izolatın tanımlanmasında, MT 80 agardaki morfolojik özellikleri yardımcı olmuş ve böylece toplam 186 (%88.1) izolat tür düze-yinde tanımlanmıştır. Morfolojik bulguların tanımlamaya eklenmesi, oranın %75.4'ten %88.1'e yükselmesini sağlamış; ancak bu artış istatistiksel olarak anlamlı bulunmamış-tır (p= 0.31).…”
Section: Introductionunclassified
“…The main characteristics of the 26 studies (32-57), which were published between 1993 and 2014, are shown in Table 1 (see also Table S2 in the supplemental material). Among the 26 studies, 12 (32-34, 36-38, 40-43, 45, 54) reported on the identification performance of the AuxaColor system, 5 (35,38,39,43,54) reported on the identification performance of the API ID32C system, and 13 (44,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) reported on the identification performance of the Vitek 2 system operating with the ID-YST (fluorimetric) card (44,(46)(47)(48)(49) and/or the YST (colorimetric) card (47,48,(50)(51)(52)(53)(54)(55)(56)(57); among them, three were direct-comparison studies, of which two were between the AuxaColor and API ID32C systems (38,43) and one was among the AuxaColor, API ID32C, and Vitek 2 systems (54). Two studies evaluating the Vitek 2 system compared the colorimetric YST card with the older fluorimetric ID-YST card (47,48); however, we decided to include the results of these studies only with respect to the YST card.…”
Section: Resultsmentioning
confidence: 99%
“…In 3 of these studies (46,48,52), phenotypic methods were used in conjunction with molecular methods (i.e., sequencing of the internal transcribed spacer [ITS] region or the 18S-28S intersequence of ribosomal DNA [rDNA]) but only to resolve discrepant results between two phenotypic methods (i.e., the method under evaluation and that used as the reference method). Among the studies that employed molecular methods as reference methods (35,51,(53)(54)(55)(56), one study employed multilocus microsatellite-based PCR fingerprinting, and rDNA sequencing of all isolates was performed in the other 5 studies.…”
Section: Resultsmentioning
confidence: 99%